Peanut Allergy, Allergen Composition, and Methods of Reducing Allergenicity: A Review - Yang Zhou; Jin-shui Wang; Xiao-jia Yang; Dan-hua Lin; Yun-fang Gao; Yin-jie Su; Sen Yang; Yan-jie Zhang; Jing-jing Zheng (International Journal of Food Science)
Peanut allergy affects 1-2% of the world's population. It is dangerous, and usually lifelong, and it greatly decreases the life quality of peanut-allergic individuals and their families. In a word, peanut allergy has become a major health concern worldwide. Thirteen peanut allergens are identified, and they are briefly introduced in this paper. Although there is no feasible solution to peanut allergy at present, many methods have shown great promise. This paper reviews methods of reducing peanut allergenicity, including physical methods (heat and pressure, PUV), chemical methods (tannic acid and magnetic beads), and biological methods (conventional breeding, irradiation breeding, genetic engineering, enzymatic treatment, and fermentation).